Комбінована дія паклітакселю та селективного інгібітора NFκB дегідроксиметилепоксиквіноміцину на клітини фолікулярного раку щитовидної залози - Пушкарьов, В.М.; Старенький, Д.В.; Гончарук, В.М.; Ямашита, С.; Саєнко, В.О.; Тронько, М.Д. (Видавничий дім "Академперіодика" НАН України, 2008)
A novel nuclear factor kappa B (NFκВ) inhibitor, dehydroxymethylepoxyquinomicin, is found to enhance the cytotoxic effect of an anticancer drug paclitaxel in the FRO cell line derived from nondifferentiated thyroid carcinoma of the follicular origin. A strong activation of caspases and PARP cleavage, as well as the decreased levels of small proteins-suppressors of apoptosis, are observed when cells are treated with a combination of both drugs. Of note are the singular paclitaxel treatment induced NF В activation and the NFκВ-dependent phosphorylation of cRaf-1, an upstream kinase of ERK1/2 which is a key member of the mitogen-activated signaling cascade that may comprise an additional NFκВ-induced antiapoptotic pathway. Thus, the combination of paclitaxel and NFκВ inhibitor is a promising pharmacological strategy for further preclinical trials aimed at the development of new therapeutic approaches to the treatment of nondifferentiated and anaplastic thyroid cancer.